Nurturing tomorrow’s leaders: the ISCB Student Council Symposia in 2018$d[version 1; peer review: not peer reviewed] - Parisi, Daniele; Gladbach, Yvonne S.; Gonzalo Parra, Rodrigo (F1000Research, 2019)
The Student Council of the International Society for Computational Biology (ISCB-SC) is a student-focused organization for researchers from all early career levels of training (undergraduates, masters, PhDs and postdocs) that organizes bioinformatics and computational biology activities across the globe. Among its activities, the ISCB-SC organizes several symposia in different continents, many times, with the help of the Regional Student Groups (RSGs) that are based on each region. In this editorial we highlight various key moments and learned lessons from the 14th Student Council Symposium (SCS, Chicago, USA), the 5th European Student Council Symposium (ESCS, Athens, Greece) and the 3rd Latin American Student Council Symposium (LA-SCS, Viña del Mar, Chile).
Last updated: 11 Mar 2020
Gesehen am 06.04.2020